2012
DOI: 10.1200/jco.2011.37.2938
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Anomalies in the Children of Cancer Survivors: A Report From the Childhood Cancer Survivor Study

Abstract: Our findings offer strong evidence that the children of cancer survivors are not at significantly increased risk for congenital anomalies stemming from their parent's exposure to mutagenic cancer treatments. This information is important for counseling cancer survivors planning to have children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 33 publications
6
98
0
2
Order By: Relevance
“…14 Most studies report no chromosomal abnormalities, [20][21][22][23][24] malformations, 21,24-28 congenital defects 21 or cancer 29,30 in offspring of cancer survivors, with the exceptions of Dalberg et al 15 who noted an increased risk of malformation among women who conceived after treatment for breast cancer, Winther et al 28 who noted a small (not significantly increased) risk of malformations in children with a parent who received irradiation for childhood cancer and Stahl et al 27 who observed statistically significant but modestly increased risk of major congenital abnormalities among offspring of males with a history of cancer. In accordance with these previous publications, we observed an increased mortality risk in offspring of survivors of hematological cancer, a substantial part of whom will have received radiation therapy for (non) Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…14 Most studies report no chromosomal abnormalities, [20][21][22][23][24] malformations, 21,24-28 congenital defects 21 or cancer 29,30 in offspring of cancer survivors, with the exceptions of Dalberg et al 15 who noted an increased risk of malformation among women who conceived after treatment for breast cancer, Winther et al 28 who noted a small (not significantly increased) risk of malformations in children with a parent who received irradiation for childhood cancer and Stahl et al 27 who observed statistically significant but modestly increased risk of major congenital abnormalities among offspring of males with a history of cancer. In accordance with these previous publications, we observed an increased mortality risk in offspring of survivors of hematological cancer, a substantial part of whom will have received radiation therapy for (non) Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…A refined analysis yielded similar negative results and omitted the controls, but sought a dose-response effect over a wide range of estimated doses of ionizing radiation to the survivors' gonads, as well as semi-quantitative estimates of their doses of alklyating agents. The mean dose of radiation was 126 cGy to ovaries and 26 cGy to the testes (Signorello et al 2012).…”
Section: Pre-conceptual Exposure To Cancer Therapymentioning
confidence: 99%
“…The included studies were published between 1999 and 2014, and all of them were cohort studies [4,[6][7][8][9][10][11][12][13][14][15][16][17][18]. A total of 10,717 women with radiation therapy and 11,128 women without radiation therapy from 13 studies were evaluated [4, 6-15, 17, 18].…”
Section: Resultsmentioning
confidence: 99%
“…In fertility factors, 5 studies were described about infertility [6,9.12,14, 18], 2 studies were based on AMH values [4,17], 2 studies on AOF [10,16], 3 studies on stillbirth or neonatal death [7,8,13], 2 studies on spontaneous abortion [7,12], 2 studies on congenital anomaly [7,15], 2 studies on low birth weight [7,11] and 1 study on preterm birth [11]. In radiation therapy methods, 4 studies were performed in radiation therapy without specific description [10,12,16,2], 2 studies on abd-pelvic radiation [6,7], 2 studies on ovarian radiation [8,15] and each of the 6 last studies were performed on pelvic radiation [4], abdominal or total body radiation [17], hypothalamic or pituitary radiation [14], nasopharyngeal radium irradiation [9], uterus radiation [11], uterus and ovarian radiation [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation